Using YouTube to Improve English Speaking Skills - Pristia Kandow; Zera Julia Sari (CV Grasta Glory, 2026)
Learning English through YouTube has proven to be quite effective in helping students improve their speaking skills. With the rapid growth of educational technology today, YouTube has become one of the easiest and most affordable resources for students to learn independently. This study aims to examine how much YouTube can help improve students’ pronunciation, grammar, fluency, and overall speaking ability. This research used a qualitative approach by distributing questionnaires and conducting interviews with university students. Based on previous studies and literature, this article discusses the role of YouTube by referring to Krashen’s Input Hypothesis, the importance of language exposure, and the shadowing technique. It also explains the advantages of YouTube, such as providing authentic English from native speakers, flexible learning time, and gives student motivation. Even though there are some challenges, including varieties content quality, passive learning habits, and too much reliance on memorization. The findings indicate that YouTube can significantly improve speaking skills when used often in every occasion and in a structured manner. Therefore, integrating YouTube into English language learning strategies is highly recommended.